Implementation of Artificial Intelligence to Improve Customer Service Efficiency at PT Jaya Harita Lestari - Axel Sandi Seno; Najmal Falah (International Journal of Informatics and Information Systems, 2026)
In the era of rapid digitalization, businesses are increasingly adopting Artificial Intelligence (AI) to enhance their operational efficiency and customer service. PT Jaya Harita Lestari, a procurement services company, has integrated AI technology through the PaDi UMKM platform to streamline its procurement processes and improve service delivery. This research explores how the adoption of AI-powered features such as the AI Agent and Tender Kilat has enhanced customer service efficiency. Using a case study approach, the study includes observations, interviews, and a survey to analyze the impact of AI implementation. The findings reveal that AI adoption has significantly reduced manual workloads, improved response times to customer requests, and increased overall customer satisfaction. The AI system’s automation of inquiries and procurement processes has led to faster, more transparent, and efficient services, positioning the company for better competitiveness in the digital marketplace. This study demonstrates the potential of AI to revolutionize service industries by improving operational performance and customer experience, offering a model for other businesses in the digital transformation journey.